The Influence Of Human Resources Management On Employee Engagement Mediated By Positive Emotions And Knowledge Management On 3 Star Hotel Employees In Samarinda City - Maharani, Aprilia Sintya (Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study aims to analyze the influence of Human Resources Management on Employee Engagement, mediated by Positive Emotions and Knowledge Management, among hotel employees in Samarinda city. Data were collected from 150 Hotel employees in Samarinda City using purposive sampling. Data analysis was conducted using descriptive statistics to find the mean, and hypothesis testing was performed using SEM AMOS 22. Instrument was tested for validity and reliability, where all statements were found to be valid and reliable, and model testing was conducted using Goodness of Fit. Research results show that Human Resources Management, Positive Emotions, Knowledge Management have a positive effect on Employee Engagement. Meanwhile, the role of Positive Emotions and Knowledge Management can partially mediate the influence of Human Resources Management on Employee Engagement. The managerial implication in this research is that management must maintain a leadership style by appreciating and communicating openly with employees. Apart from that, it is necessary to improve a supportive work environment and always pay attention to the balance of work and personal life. Management also needs to maintain training or workshops for employees as well as increase the dissemination of information and solutions regarding projects and problems faced.